Development of spatial-based system for business licensing for a Malaysian local town governing authority - Mohd Nor, Nurfarhana (2020)
A local authority (pihak berkuasa tempatan in Malay, PBT) is an entity that is responsible for administering internal resources and providing good infrastructure for the residents. They need to be sensitive and attentive to the rapid changes in technologies and systems in order to provide the best services and sustainable life to the people. This study which involved the development of spatial-based system for business licensing for Malaysian local authorities was conducted to help the local authorities in improving their services. The Johor Bahru City Council (MBJB) was selected as the collaborator of this study and the issues encountered by them was identified. Based on the discussions, interviews and meetings with the MBJB, the licensing business was selected as the subject matter of this study. During the user requirement study (URS), various issues related to business licensing were highlighted, which include the control of the registration and renewal of premises license, monitoring of field enforcement officers, loss of documents, and complaint management. The old methods employed by local authorities were no longer relevant and need to be replaced with new tools, new technologies and new systems to increase the revenue with more cost-free options. To bridge the research gap, a spatial-based system equipped with a global positioning satellite system was proposed. The spatial-based system was developed by integrating information and communication technology, global positioning system or global navigation satellite system and geographic information system to allow tracking and tracing of field enforcement personnel or mobile workforce, preparation of online reports, efficient complaint management, and monitoring of spatial premises registration and renewal of premises on digital maps. This study had two objectives. The first objective was to develop a spatial-based system for business licensing with the concept of mobile workforce for local authorities. The second objective was to assess the acceptance level of the local authorities on the spatial-based system by evaluating the effectiveness of the system, user readiness and organizational readiness. This study has successfully achieved the first objective as the system was successfully developed according to the URS, tested and validated. Eleven evaluation procedures were performed with 10 (90.91%) of them passed without comment and 1 (9.09%) passed with comments or corrections. Since the passing threshold was 90%, the system was considered passed and fulfilled all the requirements from MBJB. The newly developed spatial-based system offers features for better performance compared to the existing business licensing practices. The second objective of this study was achieved when the level of acceptance for system effectiveness, user readiness and organizational readiness reached 99.33%, 95.33% and 96.20% respectively, which indicated a high level of acceptance for each aspect. The overall acceptance level of the spatial-based system reached a score of 97.33%, which mean MBJB was highly satisfied to the enhanced system. This study has contributed significantly to the local authorities especially in creating smart city elements for the purpose of improving services to the community in line with the impact of the industrial revolution that will change the service landscape towards digital and global practices. The development of the spatial-based system for business licensing with the concept of mobile workforce for MBJB could be used as a reference for other local authorities or potential users at different municipal levels.